Changes in urine volume and subjective micturition during sitting posture in water - Wada, T.; Hayashi, S.; Nose, Y.; Kremenik, M. J.; Onodera, S. (XIIth International Symposium for Biomechanics and Medicine in Swimming, 2014)
The purpose of this study was to investigate the relationship of the urine volume, subjective micturition, reported thermal sensation, heart rate, blood pressure and rectal temperature during sitting posture in water.